An Analysis Of Discrimination Power, Difficulty Index, And Distracter Of English Test Items Constructed By Efl Teacher Of Eleventh Grade At Negeri 2 Senior High School Maumere - Kornelia Yosefina Lani; Maria Yulita Dhewa; Oktaviana Perada Samon; Maria Donna Chelsea; Anjelina Nidia De’e; Ana Maria Avelina (Journal of Innovative and Creativity (Joecy), 2026)
The purpose of this study is to evaluate the discrimination power, difficulty index, and effectiveness of the distractors for the English test items prepared by the EFL teacher of the eleventh grade students at SMA Negeri 2 Maumere. The present study used a descriptive qualitative approach where the objects of the research were 13 English test items and answer sheets of 20 eleventh-grade students. Data collection was done through documentation while manual analysis using item analysis formula was done to find the difficulty index, discrimination power, and distractor index of the items. It is found that concerning the discrimination power, there was one (7.7%) dropped item, seven (53.8%) items were categorized as corrected, and five (38.5%) items were categorized as good. With respect to the difficulty index, three (23.1%) items were easy, five (38.5%) were moderate, and five (38.5%) were difficult. Concerning the distractor analysis, about 12% distractors were very poor, 31% were poor, 25% were fair, 15% were good, and 19% were very good, which implies that many distractors were not effective in drawing the attention of low performing students to the wrong answers. With regards to the above findings, it can therefore be concluded that the English test items formulated by the EFL teacher do not meet the requirements of good test items with regard to discrimination and distractors and thus need further improvement.